2020
DOI: 10.1016/j.ijid.2020.09.1417
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and age distributions of SARS-CoV-2 and other coronaviruses, southeastern France

Abstract: Highlights Comparable bell-shaped distributions for SARS-CoV-2 and endemic coronaviruses. Different age distributions for SARS-CoV2 and other respiratory viruses. Less children among all SARS-CoV-2- positive than all endemic coronavirus- positive. SARS-CoV2 was the only respiratory virus to spare children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
2
8
0
1
Order By: Relevance
“…In IHU in Marseille, France, we have carried out SARS-CoV-2 RNA testing using real-time reverse transcription-PCR (qPCR) since the end of January 2020, as previously described [ 1 , 5 ]. The numbers of tests and cases were daily monitored since the first positive diagnosis on 02/27/2020 [ 2 ] ( https://www.mediterranee-infection.com/covid-19/ ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In IHU in Marseille, France, we have carried out SARS-CoV-2 RNA testing using real-time reverse transcription-PCR (qPCR) since the end of January 2020, as previously described [ 1 , 5 ]. The numbers of tests and cases were daily monitored since the first positive diagnosis on 02/27/2020 [ 2 ] ( https://www.mediterranee-infection.com/covid-19/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The SARS-CoV-2 virus emerged in humans in Wuhan, China, in December 2019, prior to speading worldwide. In China and Europe, the epidemic had a bell shape typical of a respiratory virus ( https://covid19-country-overviews.ecdc.europa.eu/ ) [ 1 , 2 ]. Surprisingly, in the countries that closed their borders, the evolution varied: in some countries, no other epidemic was detected whereas in others, new epidemic waves occurred, caused by new variants [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 epidemic exhibited a bell-shaped incidence curve [24] (https:// www.newsbeast.gr/files/1/2020/05/COVID19PredictionPaper. pdf) (https://coronavirus.jhu.edu/data/new-cases; https:// www.mediterranee-infection.com/covid-19/; Figure 2), which is a typical epidemic curve [25]. In Western countries, in the Northern hemisphere, the outbreak decreased dramatically during the spring, as is the case for epidemics arising from other respiratory viruses.…”
Section: Sars-cov-2 Epidemiologymentioning
confidence: 95%
“…Moreover, SARS-CoV-2 affected people differently according to their age. Very few cases and less severe outcomes were observed in children [25][26][27][28][29][30][31][32][33], while SARS-CoV-2 infections have been more prevalent and severe in the elderly. For instance, a large study conducted in Iceland on the general population reported that children under the age of 10 were half as likely to be diagnosed with SARS-CoV-2 than children over the age of 10 or adults [32].…”
Section: Sars-cov-2 Epidemiologymentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic that started in Wuhan, China in December 2019 has spread rapidly around the world (https://coronavirus.jhu.edu/ map.html). At the Méditerranée Infection Institute (IHU) in Marseille, routine diagnosis of SARS-CoV-2 by PCR was set up in January 2020 (Lagier et al, 2020;Colson et al, 2020a). The first SARS-CoV-2-infected patient was diagnosed at the IHU on February 27, 2020 (Colson et al, 2020c) (https://www.mediterranee-infection.com/covid-19/).…”
Section: Introductionmentioning
confidence: 99%